Does citizen participation in budget allocation pay? A survey experiment on political trust and participatory governance - Martin Ardanaz; Susana Otálvaro-Ramírez; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2022)
Participatory programs can reduce the informational and power asymmetries that engender mistrust. These programs, however, cannot include every citizen. Hence, it is important to evaluate if providing information about those programs could affect trust among those who do not participate. We assess the effect of an informational campaign about these programs in the context of a survey experiment in the city of Buenos Aires, Argentina. Results show that providing detailed information about citizen involvement and outputs of a participatory budget initiative marginally shapes voters' assessments of government performance and political trust. Effects are larger for individuals with ex ante more negative views about the local government's quality and differ according to respondents' beliefs about the ability of their communities to solve the type of collectiveaction problems the program seeks to address. This paper complements the literature that has examined the effects of participatory interventions on trust, and the literature that evaluates the role of information. The results suggest that participatory budget programs could directly affect budget allocations and trust for those who participate, and those that are well-disseminated could also affect trust in the broader population. Because mistrustful individuals tend to shy away from demanding the government public goods that increase overall welfare, well-disseminated participatory budget programs could affect budget allocations directly and through their effect on trust. Investing in these programs and their dissemination may be worthwhile.
Keywords: C90; D70; D90; H72; P16; 330; Participatory governance; Collective decision-making; Trust; Survey experiment; Local governments; Political economy